Bulk Loading of Calcium Indicator Dyes to Study Astrocyte Physiology: Key Limitations and Improvements Using Morphological Maps - Reeves, Alexander M. B. (Society for Neuroscience, 2011)
Calcium signaling has been studied in astrocyte cell bodies using bulk loading of calcium indicator dyes, and astrocytes are known to display intracellular calcium transients. An assumption in recent data on the neuronal impact of somatic astrocyte calcium transients has been that bulk loading reflects signaling in relevant astrocyte compartments such as processes. We assessed bulk loading using Sholl analysis (Sholl, 1953) of astrocytes loaded with common calcium indicator dyes and compared these data with Sholl analysis of astrocyte morphology. In the CA1 region of the hippocampus from rats, we found that bulk loading of calcium indicator dyes only reports on calcium signals within the soma and in the most proximal processes, leaving ∼90% of the area of an astrocyte and its extensive processes unsampled. By using morphological reconstructions as “maps” after the imaging session, we present simple procedures that remedy these shortfalls and permit reliable detection of calcium transients in distal astrocyte processes. The data thus reveal limitations in the interpretation of astrocyte calcium imaging data gathered with bulk loading and provide refinements to minimize these shortcomings.